2013
DOI: 10.1016/j.joi.2012.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Would it be possible to increase the Hirsch-index, π-index or CDS-index by increasing the number of publications or citations only by unity?

Abstract: The aim of the study is to explore the effects of the increase in the number of publications or citations on several impact indicators by a single journal paper or citation. The possible change of the h-index, A-index, R-index, -index, -rate, Journal Paper Citedness (JPC), and Citation Distribution Score (CDS) is followed by models. Particular attention is given to the increase of the indices by a single plus citation. The results obtained by the "Successively Built-up Indicator" model show that with increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 27 publications
0
7
0
1
Order By: Relevance
“…where we set the cbias as 0 if the self-citations are less than 5% of the citations for respective paper and cbias is set to the biased value exceeding the 5% limit otherwise. From Equations (2,4,6), net-citations (denoted by ncit) can simply be calculated as, ncit = gcit − f j (jbias) + f a (abias) + f c (cbias) .…”
Section: Co-author Biasmentioning
confidence: 99%
See 1 more Smart Citation
“…where we set the cbias as 0 if the self-citations are less than 5% of the citations for respective paper and cbias is set to the biased value exceeding the 5% limit otherwise. From Equations (2,4,6), net-citations (denoted by ncit) can simply be calculated as, ncit = gcit − f j (jbias) + f a (abias) + f c (cbias) .…”
Section: Co-author Biasmentioning
confidence: 99%
“…In this work, the author has evaluated 20 variants on the dataset of mature scientists and found that ranking the publications based on their number of citations is not a very useful tool. In [4], it is observed that the score of various indices under study increases the number of publications. In [5], 108 variants have been reviewed to find out correlation among those articles.…”
Section: Introductionmentioning
confidence: 99%
“…VM konusunda bildiri makalelerine en fazla yer veren (Thomson and Reuters tarafından taranan-Conference Proceedings Citation Index) konferanslar şunlardır: Bilindiği üzere internet teknolojisindeki gelişmelere paralel olarak; bilimsel dergiler de çevrim içi makale başvuru ve hakemlik/değerlendirme sistemleriyle süreçleri kolaylaştırma çabasına girmişlerdir. Benzer şekilde; araştırmacılar da kaynaklara daha kolay erişebilir bir hale gelmiş ve makale başvuru sayılarında/yayınlanan makale sayılarında ciddi artışlar yaşanmıştır (Vinkler, 2013). Bu nedenle; bir bilimsel alandaki gelişmeleri düzenli olarak takip edebilmek oldukça zorlu bir hal almıştır.…”
Section: şEkil 1 Vm Makalelerin Yıllar Içindeki Dağılımıunclassified
“…A different way of manipulating the H-index is by strategic self-citations [10,28]; Bartneck and Kokkelmans [3] consider approaches to detect these. Strategic self-citations take some effort and are irreversible.…”
Section: Introductionmentioning
confidence: 99%